2019
DOI: 10.1002/ajh.25582
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐CD19 chimeric antigen receptor‐modified T‐cell therapy bridging to allogeneic hematopoietic stem cell transplantation for relapsed/refractory B‐cell acute lymphoblastic leukemia: An open‐label pragmatic clinical trial

Abstract: Chimeric antigen receptor-modified T-cell (CAR-T) therapy is effective and safe for patients with relapsed/refractory B-cell acute lymphoblastic leukemia (r/r B-ALL), but its value has been limited in terms of long-term leukemia-free survival. New strategies that can help CAR-T therapy achieve lasting effect are urgently warranted. This nonrandomized interventional pragmatic clinical trial had a particular aim. It explored whether consolidative allogeneic hematopoietic stem cell transplantation (allo-HSCT) cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 43 publications
(67 reference statements)
3
97
1
1
Order By: Relevance
“…They found that the primary driver of CAR-T cell expansion and that minimizes the risk of CD19 + relapse was the cumulative burden of CD19-expressing cells, as assessed in the bone marrow prior to lymphodepleting chemotherapy. In contrast to other reports, neither the cell dose [27] nor leukemia burden [43,72] alone was a predictor of the magnitude or duration of CD19 CAR-T engraftment in this trial. The authors also suggested that a high antigen burden does not induce exhaustion of CAR T-cellsthe therapeutic cells, and that the elimination of the target cells promotes the transition of the effector cells into functional memory CAR-T cells.…”
Section: Prognostic Biomarkers Of Relapsecontrasting
confidence: 99%
See 1 more Smart Citation
“…They found that the primary driver of CAR-T cell expansion and that minimizes the risk of CD19 + relapse was the cumulative burden of CD19-expressing cells, as assessed in the bone marrow prior to lymphodepleting chemotherapy. In contrast to other reports, neither the cell dose [27] nor leukemia burden [43,72] alone was a predictor of the magnitude or duration of CD19 CAR-T engraftment in this trial. The authors also suggested that a high antigen burden does not induce exhaustion of CAR T-cellsthe therapeutic cells, and that the elimination of the target cells promotes the transition of the effector cells into functional memory CAR-T cells.…”
Section: Prognostic Biomarkers Of Relapsecontrasting
confidence: 99%
“…In patients determined as high-risk of relapse after CAR-T therapy, consolidation therapy after infusion will be imperative to prolong survival. A study conducted in our institute highlighted that CAR-T therapy following allogeneic hematopoietic stem cell transplantation (allo-HSCT) was a safe and effective therapeutic strategy for relapsed/refractory B-ALL patients, and might prolong EFS and RFS, especially in patients with high preinfusion tumor burden [72]. Hence, the identification of biomarkers is crucial for early identification, accurate intervention, and individualized management.…”
Section: Prognostic Biomarkers Of Relapsementioning
confidence: 99%
“…CAR-T therapy is a novel therapeutic strategy for r/r B-ALL patients [8][9][10]. CAR-T cells can migrate into the leukemia cell sanctuary, such as cerebrospinal fluid by overcoming the blood-brain barrier (BBB), which might be an important approach for solving the sanctuary leukemia problems with traditional chemical agents [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although CAR T-cell treatments lead to relatively controllable adverse events in R/R ALL patients, these patients still have a high risk of relapse ( 6 , 7 ). In such patients, CAR T-cell therapy could be a bridge for HSCT, providing temporary molecular remission for transplantation and improving the prognosis ( 76 ).…”
Section: Recurrence After Car T-cell Therapymentioning
confidence: 99%